Imperata grassland mapping in northern uplands of lao PDR: Area, distribution, characteristics, and implications for slash-and-burn cultivation - Bounthanh Keoboualapha (2018)
© Center for Southeast Asian Studies, Kyoto University. Slash-and-burn cultivation (SBC) is an important food and cash crop production system in mountainous regions of many countries in Southeast Asia. While links between unsustainable SBC and the formation of Imperata grassland (IGL) have been well documented, there has been limited research on the issues with the intention of providing appropriate information to communities in Laos aiming at better use of natural resources. This paper reveals the IGL area, distribution, and characteristics in the uplands of northern Laos, and discusses the importance of IGL for upland development based on the synthesis of remotely sensed Landsat-5 TM and GIS data. We have demonstrated the potential use of geoinformation technology as a set of informatics tools that can be applied in other area studies in Laos. Nineteen land uses/land covers of 196,317 hectares in Nambak District in northern Laos were mapped with an overall accuracy of 92.1% and a kappa statistic of 91.3%. IGL achieved >90% mapping accuracy. The current IGL was estimated at about 2.5% (4,878 hectares) of the district area and characterized as a “micro-grassland,” with most patch sizes being less than half a hectare. About 37% of the district area in the southeastern part was identified as the most Imperata-infested zone. The study suggests that improper SBC intensification into more permanent crop production systems is a major cause of Imperata infestation in the upland areas and that the spread of IGL can be a threat to the productivity and sustainability of traditional SBC systems and already intensified land use systems. In order to utilize land resources more effectively, government intervention is indispensable; and development efforts should initially focus on the most affected areas.